Maternal Hypothyroidism in Early Pregnancy and Infant Structural Congenital Malformations - Källén, Bengt (Hindawi Publishing Corporation, 2014)
Background. The question is debated on whether maternal hypothyroidism or use of thyroxin in early pregnancy affects the risk for infant congenital malformations. Objectives. To expand the previously published study on maternal thyroxin use in early pregnancy and the risk for congenital malformations. Methods. Data from the Swedish Medical Birth Register were used for the years 1996–2011 and infant malformations were identified from national health registers. Women with preexisting diabetes or reporting the use of thyreostatics, anticonvulsants, or antihypertensives were excluded from analysis. Risk estimates were made as odds ratios (ORs) or risk ratios (RRs) after adjustment for year of delivery, maternal age, parity, smoking, and body mass index. Results. Among 23 259 infants whose mothers in early pregnancy used thyroxin, 730 had a major malformation; among all 1 567 736 infants, 48012 had such malformations. The adjusted OR was 1.06 (95% CI 0.98–1.14). For anal atresia the RR was 1.85 (95% CI 1.00–1.85) and for choanal atresia 3.14 (95% CI 1.26–6.47). The risk of some other malformations was also increased but statistical significance was not reached. Conclusions. Treated maternal hypothyroidism may be a weak risk factor for infant congenital malformations but an association with a few rare conditions is possible.